Association between lipid accumulation product (LAP) index and self-reported oral health outcomes: a cross-sectional study - Li Shuning; Yang Wei; Fan Xuhui; Dong Jianfeng; Liu Jilun (Lipids in Health and Disease)
Abstract Background Lipid Accumulation Product (LAP) is a biomarker associated with excessive lipid accumulation and various metabolic diseases. Despite the well-established link between oral and systemic health, the association between LAP and oral health remains largely unexplored. Methods Data from 7,124 participants aged over 18 years from the National Health and Nutrition Examination Survey (NHANES) between 2009 and 2014 were analyzed. Multivariate logistic regression models were applied to evaluate the independent association between LAP and self-reported oral health outcomes, adjusting for potential confounders. Results There was a significant correlation between increasing LAP levels and deteriorating oral health status (β = 0.26, 95% CI: 0.20 to 0.32, P < 0.0001). Subgroup analyses revealed that the negative correlation between LAP and self-reported oral health outcomes was more pronounced in younger individuals and those with higher education levels. A non-linear relationship was identified, with oral health deteriorating significantly as LAP increased up to a threshold of 83, after which the relationship became non-significant. Conclusions This study demonstrates a robust association between LAP and self-reported oral health outcomes, suggesting that LAP could be a reliable indicator for assessing oral health status. The findings highlight the importance of targeted health interventions for populations with higher LAP indices to prevent oral health deterioration and potential systemic health issues.